Elaboración de estrategias de educación ambiental que fomenten actitudes positivas hacia la conservación de abejas solitarias, en estudiantes de primaria de la parroquia Purunuma cantón Gonzanamá - Ayora Quito, Juana Mercedes (2023)
The current research seeks to determine the incidence of educational strategies in the change of attitudes towards solitary bees in environmental students of the “Purunuma Educational Unit”, through the generation of significant experiences and emotional affinity towards solitary bees. The methodology applied in this research had a quantitative, quasi-experimental, descriptive approach; For data collection, the technique used was the survey (Children's Environmental Perceptions Scale), which is measured using a Likert scale from 1 (totally disagree) to 5 (totally agree), which was addressed to second-year students. to fifth grade of primary school of the institution. While the educational strategy consisted of 5 weekly workshops, in which the participants acquired knowledge about solitary bees and cognitive skills that are related to their life context. A change was achieved in the attitudes of the participants towards solitary bees, since, initially, a biophobic attitude towards these pollinators was observed, while after the educational strategy a biophilic attitude was observed. Demonstrating that an educational strategy focused on solitary bees contributes positively to changing attitudes towards these pollinators. Keywords: environmental education, solitary bees, pollinators, biophilia, biophobia.